Helmintos gastrointestinais de duas populações de pombos de vida livre (Columba livia) no Brasil - Vaz, Frederico Fontanelli; da Silva, Lidiane Aparecida Firmino [UNESP]; Ferreira, Vivian Lindmayer; da Silva, Reinaldo José [UNESP]; Raso, Tânia Freitas (FapUNIFESP (SciELO), 2017)
The present study analyzed gastrointestinal helminth communities in 265 wild pigeons (Columba livia) living in the municipalities of São Paulo and Tatuí, state of São Paulo, Brazil, over a one-year period. The birds were caught next to grain storage warehouses and were necropsied. A total of 790 parasites comprising one nematode species and one cestode genus were recovered from 110 pigeons, thus yielding an overall prevalence of 41.5%, mean intensity of infection of 7.2 ± 1.6 (range 1-144) and discrepancy index of 0.855. Only 15 pigeons (5.7%) presented mixed infection. The helminths isolated from the birds were Ascaridia columbae (Ascaridiidae) and Raillietina sp. (Davaineidae). The birds’ weights differed according to sex but this did not influence the intensity of infection. The overall prevalence and intensity of infection did not differ between the sexes, but the prevalence was higher among the birds from Tatuí (47.8%). The gastrointestinal helminth community of C. livia was characterized in the two areas studied and parasite homogeneity was observed over the 12 months analyzed at both locations. These results make contributions to the current literature on health aspects of wild C. livia populations.
Gastrointestinal helminths of two populations of wild pigeons (Columba livia) in Brazil
Keywords: Ascaridia; Cestodes; Columbiformes; Helminthology; Nematodes; Raillietina